HUBUNGAN PENGETAHUAN DENGAN SIKAP REMAJA PUTRI TENTANG PEMERIKSAAN PAYUDARAH SENDIRI DI SMA NEGERI 7 TANJUNG BALAI TAHUN 2019 - Herlia Sumardha Nasution; Nila Hayati; Ade (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2020)
Breast cancer is the most feared breast disorder for women, because this disease can not be cured if found at an advanced stage of women is needed to know about breast cancer the purpose of this study is to know there is a Relationship between Knowledge and Attitudes of Young Women About Breast Examination at 7 Tanjung High School Balai Balai 2019